How to Measure Radiographic Anterior Tibial Translation and its Effect on Anterior Cruciate Ligament Tears - Ling Yang; Cheng-Pang Yang; Chieh-An Chuang; Yi-Sheng Chan (Formosan Journal of Musculoskeletal Disorders)
Anterior tibial translation (ATT) has been used in detecting anterior cruciate ligament tear due to anterior subluxation of tibia relative to the femur. This could be done with both X-ray and magnetic resonance imaging. However, both the method and cutoff value of this measurement were variable in different studies. In this review article, we reviewed different methods of ATT measurement. Further research to standardize ATT measurement is necessary.